Phytobezoar as a Cause of Recurrent Obturation Intestinal Obstruction. A Clinical Case in Surgical Practice - A. G. Hasanov; R. R. Fayazov; R. R. Garaev; D. G. Shaibakov; E. R. Ibatullin; R. R. Shayakhmetov (Креативная хирургия и онкология)
Introduction. Phytobezoar refers to a foreign body accumulated in the stomach when swallowing substances of natural or synthetic origin. Phytobezoar is formed in the stomach and small intestine, its etiopathogenesis is yet to be investigated. It causes obturation intestinal obstruction, which requires emergency surgical intervention. The paper presents a clinical case in surgical practice of phytobezoar in the small intestine which was complicated by a recurrent obturation intestinal obstruction. Aim: to present a clinical case of phytobezoar in the form of recurrent obturation intestinal obstruction. Materials and methods. 66years old female patient Kh. underwent surgical treatment for obturation intestinal obstruction caused by phytobezoar twice within a short period of time. The gastric resection and consumption of bezoar-dangerous products due to a driedfruit diet were considered to be the prerequisite for the formation of phytobezoar. According to the pathomorphologic examination, the intervention included laparotomy, enterotomy and phytobezoar extraction. Results and discussion. A complete revision of the abdominal cavity organs was performed during the first laparotomy with no other fragments of phytobezoar found. Following the first surgery and before discharge, the patient underwent ultrasound, CT scan of abdominal cavity organs, fibrogastroscopy — no volumetric pathologic formations in the abdominal cavity were detected. Therefore, the phybobezoar was assumably formed again in a relatively short period of time and led to the development of reobstruction. The patient was discharged with recovery.Conclusion. The clinical case shows that in surgical practice phytobezoar can get formed repeatedly in a short period of time and lead to the development of recurrent intestinal obstruction.